A remarkable and durable response to tislelizumab treatment of an anaplastic thyroid carcinoma without targetable genomic alterations: a case report - Chai, Jingjing; Lv, Jiaqi; Xiong, Jian; Chen, Xiuwen; Luo, Senyuan; Luo, Zhiguo; Luo, Ming (Frontiers in Immunology, 2025)
Anaplastic thyroid carcinoma (ATC) is a rare and highly aggressive malignancy characterized by a poor prognosis, with a median survival time of approximately 3 to 4 months. In this report, we present a case involving a 59-year-old patient diagnosed with ATC, who experienced swift local recurrence and pulmonary metastasis following radical thyroidectomy. Comprehensive Sanger sequencing of the resected tumor tissue revealed no mutations in the TERT promoter or the BRAF V600E gene. The patient exhibited rapid recurrence post-surgery and was deemed unsuitable for immediate surgical intervention. The patient was unable to tolerate chemotherapy; therefore, radiotherapy was administered initially to prevent airway compression resulting from disease progression. During the course of radiotherapy, pulmonary metastasis developed, yet the patient remained intolerant to both chemotherapy and anti-angiogenic therapy. Immunohistochemical analysis revealed a high expression of PD-L1. Whole exome sequencing (WES) indicated a tumor mutation burden (TMB) of 2.98 mut/Mb, microsatellite stability (MSS), and identified 10 missense mutations, 1 nonsense mutation, and 1 frameshift insertion. However, none of these mutations have corresponding targeted therapies. Consequently, we administered tislelizumab as an immunotherapeutic intervention. The patient exhibited significant regression in cervical metastatic lymph nodes and pulmonary metastatic tumors, achieving a sustained remission lasting 14 months, culminating in complete remission, without experiencing any adverse events related to immune checkpoint inhibitors. This case demonstrates the efficacy of second-line monotherapy with an immune checkpoint inhibitor (ICI) for ATC in a patient unable to tolerate chemotherapy and anti-angiogenic anlotinib treatment, thereby offering a viable treatment strategy for ATC patients.